2021
DOI: 10.21037/atm-21-2488
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of valve metagenomic next-generation sequencing when applied to the etiological diagnosis of infective endocarditis

Abstract: Background: Metagenomic next-generation sequencing (mNGS) is widely applied in the etiological diagnosis of infectious diseases. However, the clinical practice of mNGS in infective endocarditis (IE) is relatively less studied. This research aimed to assess the etiological diagnostic value of valve mNGS in IE.Methods: We retrospectively analyzed 49 IE patients who underwent cardiac valve surgery in Zhongshan Hospital, Fudan University, Shanghai from 1 June 2018 to 30 November 2020. Among these IE patients, 28 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…To RK and colleagues, for example, reported that four of eight IE patients underwent revision of antimicrobial regimens, based on mNGS results, to enhance the likelihood of treatment success [ 19 ]. This was also the case in the study of Cai S et al, where antibiotic therapy was de-escalated to cephalosporin and aminoglycosides for six culture-negative IE subjects following pathogen identification by valve mNGS screening of valve tissue [ 15 ]. In addition, mNGS may be also important in enhancing antimicrobial stewardship, and reducing both adverse drug events and selection for antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…To RK and colleagues, for example, reported that four of eight IE patients underwent revision of antimicrobial regimens, based on mNGS results, to enhance the likelihood of treatment success [ 19 ]. This was also the case in the study of Cai S et al, where antibiotic therapy was de-escalated to cephalosporin and aminoglycosides for six culture-negative IE subjects following pathogen identification by valve mNGS screening of valve tissue [ 15 ]. In addition, mNGS may be also important in enhancing antimicrobial stewardship, and reducing both adverse drug events and selection for antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 90%
“…However, it remains essential to correlate the mNGS to the clinical context of the patient as there may be false positives as suggested in some studies possibly due to laboratory contamination or detection of normal skin flora [ 15 , 16 , 23 ]. Sequencing results include many parameters that reflect the number of distinct and unique sequences aligned to a microorganism’s genome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 21 patients (42.9%) had negative culture results. For all patients, including culture-negative IE patients, receiving empirical antibiotic treatment, the causative IE pathogen could be detected with mNGS ( Cai et al, 2021 ).…”
Section: Investigative Research Approachesmentioning
confidence: 99%